Tuning of heat and charge transport by Majorana fermions - Ricco, L. S. [UNESP]; Dessotti, F. A. [UNESP]; Shelykh, I. A.; Figueira, M. S.; Seridonio, A. C. [UNESP] (Springer Nature, 2018)
We investigate theoretically thermal and electrical conductances for the system consisting of a quantum dot (QD) connected both to a pair of Majorana fermions residing at the edges of a Kitaev wire and two metallic leads. We demonstrate that both quantities reveal pronounced resonances, whose positions can be controlled by tuning of an asymmetry of the couplings of the QD and a pair of MFs. Similar behavior is revealed for the thermopower, Wiedemann-Franz law and dimensionless thermoelectric figure of merit. The considered geometry can thus be used as a tuner of heat and charge transport assisted by MFs.